2021
DOI: 10.48121/jihsam.844959
|View full text |Cite
|
Sign up to set email alerts
|

A Research to Determine the Ethical Climate Perception of Nurses Who Work In Private Hospitals

Abstract: Objective: It's imperative that organizations that want to exist in the business world where competition is intense and that want to ensure should create a positive ethical climate perception. The aim of this study was to determine the level of perceptions of the ethical climate of nurses who work in a private hospital and to determine whether ethical climate perceptions differ according to demographic characteristics.Methods: This is a descriptive cross-sectional study. The study was conducted between July-Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Concerning the distribution of the ethical climate dimensions, the study results indicated that most of the studied sample has a negative perception about self-interest dimension; this may be due to heavy the shortage of staff nurses and heavy workload, this result agreed with [ 24 ] who confirmed that the most positive perception of participants was to patients.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Concerning the distribution of the ethical climate dimensions, the study results indicated that most of the studied sample has a negative perception about self-interest dimension; this may be due to heavy the shortage of staff nurses and heavy workload, this result agreed with [ 24 ] who confirmed that the most positive perception of participants was to patients.…”
Section: Discussionsupporting
confidence: 81%
“…The ethical climate acts as a guide for staff members to understand the acceptable and unacceptable actions, assisting them in making more informed judgments. Moreover, it can affect the willingness of nurses to continue their job duties [ 24 ]. Therefore, this study was conducted to explore the relation between innovative work behavior and ethical climate perceptions among nursing personnel.…”
Section: Introductionmentioning
confidence: 99%
“…In the same vein, Das and Dasgupta (2019) found significant differences in age groups in relation to consumers' perception of ethical issues in advertisement messages. The study by Avçi̇n et al. (2021) which sought to determine whether or not differences exist in ethical perception among nursing employees in public hospitals, found no significant perceptual differences with respect to age.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…found significant differences in age groups in relation to consumers' perception of ethical issues in advertisement messages. The study byAvçi_n et al (2021) which sought to determine whether or not differences exist in ethical perception among nursing employees in public hospitals, found no significant perceptual differences with respect to age. On their part,Sweeney et al (2010) reported a significant inverse relationship between age and the intention to engage in premature sign-off among pre-manager level auditors, whileMusbah et al (2016) found no significant difference in the ethical behaviour of Libyan management accountants based on their age.Musbah et al's (2016) finding is similar to previous studies (e.g Kuntz et al, 2013;Pierce and Sweeney, 2010).…”
mentioning
confidence: 99%